Analisis Pengaruh Perilaku Inovatif dan Self – Esteem terhadap Organizational Citizenship Behavior di PT. Stannia Binekajasa - Jerry Marcellinus Logahan; Aditya Indrajaya; Astrid Wahyu Proborini (Binus Business Review, 2014)
This research was conducted in PT. Stannia Binekajasa, a company engaged in apartment leasing and sport facilities service. The purpose of this study is to determine the effect of Innovative Behavior and Self -Esteem on Organizational Citizenship Behavior both partially and simultaneously. The data obtained by survey, using questionnaire through cross sectional method. The data is processed using simple regression and multiple regression analysis as a method analysis. The result of this study indicates that the Innovative Behaviour in the company, have a significant influence on Organizational Citizenship Behavior by 79.5%, and Self-Esteem have a significant influence on Organizational Citizenship Behavior by 89.5%. Variable Innovative Behavior and Self- Esteem in the company have a significant influence on Organizational Citizenship Behavior by 89.2%.